Screening and pharmacodynamic evaluation of the antirespiratory syncytial virus activity of steroidal pyridine compounds in vitro and in vivo. Issue 6 (1st November 2020) - Wang, Zhenya; Hou, Duoduo; Fang, Jieyu; Zhu, Li; Sun, Yingying; Tan, Yayun; Gu, Zichen; Shan, Lihong
Abstract: Respiratory syncytial virus (RSV) causes serious lower respiratory tract infections and there are currently no safer or more effective drugs available. It is important to find novel medications for RSV infection. A series of steroidal pyridines were synthesized for screening and evaluation of their antiviral activity and investigation of their antiviral mechanism of action. Compound 3l had the highest antiviral activity, with a half‐maximal effective concentration (EC50 ) of 3.13 μM. Compound 3l was explored for its effects in vitro on RSV 2 h before infection (pretreatment), at the time of infection (competition), and 2 h after infection (postinfection). Toll‐like receptor (TLR)‐3, retinoic acid‐inducible gene (RIG)‐I, interleukin (IL)‐6, and interferon (IFN)‐β were suppressed at the cellular level. Mouse lung tissue was subjected to hematoxylin and eosin (HE) staining and immunohistochemistry, which showed that RSV antigen and M gene expression could be reduced by compound 3l . Decreased expression of TLR‐3, RIG‐I, IL‐6, IFN‐β, and IL‐10 was also found in vivo. The results indicated that compound 3l exerted its antiviral effects mainly through inhibition of viral replication and downregulation of inflammatory factors.